2015
DOI: 10.1039/c5nr03841c
|View full text |Cite
|
Sign up to set email alerts
|

Visible to near-infrared plasmon-enhanced catalytic activity of Pd hexagonal nanoplates for the Suzuki coupling reaction

Abstract: Photocatalytic conversion of solar energy to chemical energy is an efficient process in green chemistry because it facilitates room temperature chemical transformations by generating electronically excited states in photocatalysts. We report here on the robust synthesis, detailed structural characterization, and especially photocatalytic properties of plasmonic Pd hexagonal nanoplates for chemical reactions. The Pd hexagonal nanoplates are twin crystals, and composed of the top and bottom faces enclosed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Several studies on plasmonic catalysis and LSPR‐mediated catalytic transformations have focused on the demonstration of this phenomenon, quantification of reaction rates, and investigation of plasmonic enhancement mechanisms towards a variety of transformations (oxidation, couplings and reductions, for example) . For instance, it has been demonstrated that the main mechanisms by which LSPR excitation can accelerate or mediate these transformations may occur due to localized heating and charge transfer (direct and indirect pathways) as a result of LSPR excitation ,,.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on plasmonic catalysis and LSPR‐mediated catalytic transformations have focused on the demonstration of this phenomenon, quantification of reaction rates, and investigation of plasmonic enhancement mechanisms towards a variety of transformations (oxidation, couplings and reductions, for example) . For instance, it has been demonstrated that the main mechanisms by which LSPR excitation can accelerate or mediate these transformations may occur due to localized heating and charge transfer (direct and indirect pathways) as a result of LSPR excitation ,,.…”
Section: Introductionmentioning
confidence: 99%
“…1a): (1) synthesis of monodisperse Pd nanocubes (NCs) ( Fig. 1b and S1a-f †); 16,17 (2) homogeneous growth of FeO x shells on Pd NCs (Fig. 1c, S1g and Table S2 †); 18 (3) reduction-diffusion of Pd/FeO x core/shell (Pd@FeO x ) NCs under the ow of 4% H 2 gas (Ar balance) ( Fig.…”
Section: Synthesis Of L1 0 -Fepd/a-fe Ncmsmentioning
confidence: 99%
“…It was reported that Pd nanoplates (twin crystals and their top and bottom faces are enclosed by {111} facets with stacking faults and side surfaces surrounded by a mixture of six {111} and six {100} facets) exhibited clear and well‐defined LSPR features . The LSPR peaks of Pd nanoplates were assigned to the longitudinal mode and could be tuned from 382 nm to 618 nm by changing the edge lengths from 31.7±10.5 nm to 60.4±19.3 nm while the thickness remains unchanged, which enabled direct harvesting of visible to near‐infrared light for catalytic Suzuki C−C cross‐coupling reactions.…”
Section: Pd Based Plasmonic Photocatalysts For Visible‐light C−c Crosmentioning
confidence: 99%
“…Plasmonic Ag based bimetallic nanostructures were also employed in photocatalyzed cross-coupling reaction. In the work reported by Verma and coworkers, [16] the Pd/Ag bimetallic nanostructures with different size and morphology were [18] The LSPR peaks of Pd nanoplates were assigned to the longitudinal mode and could be tuned from 382 nm to 618 nm by changing the edge lengths from 31.7 � 10.5 nm to 60.4 � 19.3 nm while the thickness remains unchanged, which enabled direct harvesting of visible to near-infrared light for catalytic Suzuki CÀ C cross-coupling reactions. Upon plasmon excitation, the catalytic Suzuki CÀ C coupling reactions were accelerated by plasmon induced hot electrons.…”
Section: Pd Based Plasmonic Photocatalysts For Visible-light Cà C Cromentioning
confidence: 99%